Obesity-dependent molecular alterations in fatal COVID-19: A retrospective postmortem study of metabolomic profile of adipose tissue - Pilger, Bruna I.; Castro, Alex; Vasconcellos, Franciane F.; Moura, Karen F.; Signini, Étore De Favari; Marqueze, Luis Felipe B.; Fiorenza-Neto, Edson A.; Rocha, Mateus T.; Pedroso, Giulia S.; Cavaglieri, Claudia R.; Ferreira, Antonio G.; Figueiredo, Caique [UNESP]; et al. (Wiley, 2024)
We investigated the effects of obesity on metabolic, inflammatory, and oxidative stress parameters in the adipose tissue of patients with fatal COVID-19. Postmortem biopsies of subcutaneous adipose tissue were obtained from 25 unvaccinated inpatients who passed from COVID-19, stratified as nonobese (N-OB; body mass index [BMI], 26.5 ± 2.3 kg m−2) or obese (OB BMI 34.2 ± 5.1 kg m−2). Univariate and multivariate analyses revealed that body composition was responsible for most of the variations detected in the metabolome, with greater dispersion observed in the OB group. Fifteen metabolites were major segregation factors. Results from the OB group showed higher levels of creatinine, myo-inositol, O-acetylcholine, and succinate, and lower levels of sarcosine. The N-OB group showed lower levels of glutathione peroxidase activity, as well as higher content of IL-6 and adiponectin. We revealed significant changes in the metabolomic profile of the adipose tissue in fatal COVID-19 cases, with high adiposity playing a key role in these observed variations. These findings highlight the potential involvement of metabolic and inflammatory pathways, possibly dependent on hypoxia, shedding light on the impact of obesity on disease pathogenesis and suggesting avenues for further research and possible therapeutic targets.
Keywords: hypoxia; inflammation; metabolome; obesity; oxidative stress